Utility of Cluster of Differentiation 5 and Cluster of Differentiation 117 Immunoprofile in Distinguishing Thymic Carcinoma from Pulmonary Squamous Cell Carcinoma: A Study on 1800 Nonsmall Cell Lung Cancer Cases - Jha, Vidya; Sharma, Preeti; Mandal, Ashish (Indian Journal of Medical and Paediatric Oncology, 2017)
Background: Mediastinum harbors a mixed bag of neoplastic lesions with varied therapeutic and prognostic implications. Distinguishing pulmonary squamous cell carcinoma from thymic carcinoma is a challenging task owing to rather nonspecific clinicoradiological features and a considerable overlap in histomorphological features. Thus, we evaluated the diagnostic utility of cluster of differentiation 5 (CD5) and CD117 immunohistochemical markers in distinguishing these tumors. Materials and Methods: The archives of department of histopathology were retrospectively reviewed from June 2012 to May 2016. Formalin-fixed paraffin-embedded blocks of 1800 cases diagnosed as nonsmall cell lung carcinoma were retrieved, and immunohistochemical expression of CD5 and CD117 was evaluated in these cases. Results: Adenocarcinoma (980; 54.44%) was the mostcommon histological subtype of lung carcinoma observed in our study. CD117 was positive in 171 out of 1800 cases (9.5%) of which 120 cases (70.17%) were adenocarcinoma, followed by 40 cases (23.4%) of squamous cell carcinoma. Immunoreactivity for CD5 was observed in 209 cases (11.61%), 200 (95.7%) cases of which were diagnosed as adenocarcinoma. None of the cases diagnosed as squamous cell carcinoma on histomorphology showed CD5 immunoexpression. Conclusion: While thymic squamous cell carcinomas are well known for CD5 and CD117 coexpression, none of the cases of squamous cell carcinoma arising in lung express CD5. These markers are a diagnostic tool to distinguish a primary lung squamous cell carcinoma from thymic carcinoma, particularly in the setting of a central pulmonary lesion with mediastinal involvement.
Keywords: Cluster of differentiation 117; cluster of differentiation 5; nonsmall cell lung cancer; thymic carcinoma